Turning of compacted graphite iron using commercial tiN coated Si 3N4 under dry machining conditions - Souza, J. V C; None, M. C A; Ribeiro, M. V. [UNESP]; Silva, O. M M; Lanna, M. A. (Trans Tech Publications, 2008)
Due to their high hardness and wear resistance Si3N4 based ceramics are one of the most suitable cutting tool materials for machining hardened materials. Therefore, their high degree of brittleness usually leads to inconsistent results and sudden catastrophic failures. Improvement of the functional properties these tools and reduction of the ecological threats may be accomplished by employing the technology of putting down hard coatings on tools in the state-of-the-art PVD processes, mostly by improvement of the tribological contact conditions in the cutting zone and by eliminating the cutting fluids. However in this paper was used a Si3N4 based cutting tool commercial with a layer TiN coating. In this investigation, the performance of TiN coating was assessed on turning used to machine an automotive grade compacted graphite iron. As part of the study were used to characterise the performance of cutting tool, flank wear, temperature and roughness. The results showed that the layer TiN coating failed to dry compacted graphite iron under aggressive machining conditions. However, using the measurement of flank wear technique, the average tool life of was increased by VC=160 m/min.The latter was also observed using a toolmakers microscope and scanning electron microscopy (SEM).
Keywords: Compacted graphite iron; Cutting tool coating; Surface roughness; Temperature; Automotive grades; Catastrophic failures; Cutting zones; Dry machining; Flank wears; Functional properties; Hardened materials; High hardnesses; Machining conditions; Pvd processes; Tool lives; Tool materials; Tribological contacts; Coated materials; Coatings; Cutting fluids; Fracture mechanics; Friction; Graphite; Hard coatings; Machine tools; Machinery; Machining; Metal working tools; Powders; Scanning electron microscopy; Silicon; Surface properties; Technology; Tin; Titanium compounds; Titanium nitride; Turning; Wear resistance; Cutting tools